Spindex Industries Limited / Muhammad Amirul Firdaus Sarmadi - Sarmadi, Muhammad Amirul Firdaus (Faculty Of Chemical Engineering, 2021)
During these 17 weeks of internship, student managed gain fresh information and valuable experiences. Synturn (M) Sdn. Bhd is well maintained company which is suitable for interns to begin learning on work culture that related to our course. Plating process is one of the process where it is not thought in my university course. From this internship, I managed to gain much knowledge related to chemical engineering especially in the plating process. I also gained much knowledge on safety precaution and hazards as to make sure those are taken seriously in any task operation. This internship helped came to realise on the importance of time management. Unlike studying in college, some of the assignment or project is done in group. But the in real working environment there are to much differences. Real working environment give me is more draining physically and mentally compared to studying. In workplace, all the job need to be done on-time independently due to the I am the only one intern in this department. This internship thought myself to built confidence and managing time properly at the same time. However, thanks to this internship, I can improved myself and dealing with new people that has different characters and behaviours aside of become more independent and having good time management skill. In conclusion, the host company and especially for interns as the quality and quantity of experience and knowledge gained are very useful and applicable for student future demand.